2021
DOI: 10.1007/s11356-021-16280-5
|View full text |Cite
|
Sign up to set email alerts
|

Ayurveda Rasayana as antivirals and immunomodulators: potential applications in COVID-19

Abstract: Coronavirus disease (COVID-19) has been declared as a pandemic by the World Health Organization with rapid spread across 216 countries. COVID-19 pandemic has left its imprints on various health systems globally and caused immense social and economic disruptions. The scientific community across the globe is in a quest for digging the effective treatment for COVID-19 and exploring potential leads from traditional systems of healthcare across the world too. Ayurveda (Indian traditional system of medicine) has a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 258 publications
(281 reference statements)
0
20
0
Order By: Relevance
“…The present COVID-19 challenge has brought a refocus on the traditional systems of medicines as one of the prevention strategies in reducing pathogen exposure and enhancing an individual's immunity. Numerous studies on traditional Chinese medicines and various Asian herbs such as Tinospora cordifolia, Withania somnifera, Andrographis paniculata, Glycerrhiza glabra, Boerhaevia diffusa , and Ocimum sanctum have demonstrated their potent immunomodulatory, anti-inflammatory properties and their applications for the prevention and treatment of COVID-19 in Asian countries ( 11 13 ). Similarly, the formulations like Amla tea were found to be effective in shortening the recovery times of symptoms in COVID-19 patients and have shown an ameliorative effect on the severity of clinical signs and CRP levels ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The present COVID-19 challenge has brought a refocus on the traditional systems of medicines as one of the prevention strategies in reducing pathogen exposure and enhancing an individual's immunity. Numerous studies on traditional Chinese medicines and various Asian herbs such as Tinospora cordifolia, Withania somnifera, Andrographis paniculata, Glycerrhiza glabra, Boerhaevia diffusa , and Ocimum sanctum have demonstrated their potent immunomodulatory, anti-inflammatory properties and their applications for the prevention and treatment of COVID-19 in Asian countries ( 11 13 ). Similarly, the formulations like Amla tea were found to be effective in shortening the recovery times of symptoms in COVID-19 patients and have shown an ameliorative effect on the severity of clinical signs and CRP levels ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of iodine, the starch that was not hydrolysed by α ‐amylase due to enzyme inhibitors in the plant extracts generates a deep blue or purple zone on the TLC plate (Figure 2A–D, track 5). A prominent deep blue zone at hR F = 72 was reported in the TLC plate which can be associated with the presence of steroid (Figure 2A–D, track 5) 9,33 …”
Section: Resultsmentioning
confidence: 96%
“…7 Steroidal saponins (shatavarins I-IV), isoflavones, asparagine, and racemosol are reported as major phytoconstituents of asparagus root. [7][8][9] Several studies have revealed that A. racemosus root extract has powerful hypoglycemic and antioxidant activity, and can be used as an important source of antioxidants to assist diabetic conditions such as nephropathy. 8 High-performance thin-layer chromatography (HPTLC) is an important tool for the accurate identification of plant material through both biochemical (enzymatic) and biological (cell-based) experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though a number of plants have been tested for the antiviral activity, it would be worth investigating other plants that have been used in the age-old practices in Ayurveda, which is a traditional form of Indian medicine. In Ayurvedic form of medicine, a group of herbs are combined into formulations called Rasayana which is provided to enhance the body’s resistance to infections and other diseases ( Singh et al., 2021 ). There is a need to study the antiviral activity of those herbs which are used in traditional forms of medicine for which not much scientific evaluations have been carried out.…”
Section: Introductionmentioning
confidence: 99%